The Actions of International Economic Organizations to Solve Global Issues - Xudoyorov Rashid; Boltaeva Mokhichekhra (Zien Journals, 2022)
They arise from the uneven development of various spheres of modern human life and the contradictions that arise in people's socio-economic, political, ideological, socio-natural and other relationships. These problems have a negative and side effect on the life of all mankind
Keywords: Organizations; Economic crisis; hunger; unemployment